(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
The improved solar reactor Sol@rmet allows to investigate the reduction of MgO in presence of carbon using concentrated solar energy in low vacuum conditions close to 900 Pa. The influence of the carbon type was studied and it was shown that a carbon issued from a biomass source was a great candidate. A gradual increase of the temperature during experiment allowed to obtain promising results. Powders with a high Mg content up to 97 wt% and a high yield rate up to 50% were collected. Short time experiments at fixed locations under the focus of the solar concentrator were performed in order to obtain information on the kinetics of the carbothermal reduction of MgO. Notably, these experiments have underlined the temperature effect on the CO emission. 50 to 80% of the CO emission mainly occurred in 100 s after the beginning of the experiments. The phase boundary reaction between MgO and C appeared to be the dominant process at the initial stage of the carbothermal reduction. Calculated activation energy of this process is around 240 kJ mol-1.